The Transfer Instability Index: A Novel Metric of Emergency Department Transfer Relationships. (29th January 2015) - Kindermann, Dana R.; Mutter, Ryan L.; Houchens, Robert L.; Barrett, Marguerite L.; Pines, Jesse M.; Meisel, Zachary
Abstract Objectives In this study, the objective was to characterize emergency department (ED) transfer relationships and study the factors that predict the stability of those relationships. A metric is derived for ED transfer relationships that may be useful in assessing emergency care regionalization and as a resource for future emergency medicine research. Methods Emergency department records at transferring hospitals were linked to ED and inpatient records at receiving hospitals in nine U.S. states using the 2010 Healthcare Cost and Utilization Project State Emergency Department Databases and State Inpatient Databases, the American Hospital Association Annual Survey, and the Trauma Information Exchange Program. Using the Clinical Classification Software to categorize conditions, high transfer rate conditions were placed into nine clinical groups. The authors created a new measure, the "transfer instability index, " which estimates the effective number of "transfer partners" for each sending ED: this is designed to measure the stability of outgoing transfer relationships, where higher values of the index indicate less stable relationships. The index provides a measure of how many hospitals a transferring hospital sends its patients to (weighted by how often each transfer partner is used). Regression was used to analyze factors associated with higher values of the index. Results Sending hospitals had a median of 3.5 effective transfer partners across all conditions. The calculated transfer instability indices varied from 1 to 2.4 across disease categories. In general, higher index values were associated with treating a higher proportion of publicly insured patients: 10 and 12% increases in the Medicare and Medicaid share of ED encounters, respectively, were associated with 10 and 14% increases in the effective number of transfer partners. This public insurance effect held while studying all conditions together as well as within individual disease categories, such as cardiac, neurologic, and traumatic conditions. Conclusions United States EDs that transfer patients to other hospitals often have multiple transfer partners. The stability of the transfer relationship, assessed by the transfer instability index, differs by condition. Less stable transfer relationships (i.e., hospitals with greater numbers of transfer partners) were more common in EDs with higher proportions of publicly insured patients.